Pyroptosis: A Developing Foreland of Ovarian Cancer Treatment - Liu, Tianyi; Hou, Min; Li, Manyu; Qiu, Cheng; Cheng, Lin; Zhu, Tianyu; Qu, Jinfeng; Li, Lanyu (Frontiers in Oncology, 2022)
Ovarian cancer (OVCA) has the second highest mortality among all gynecological cancers worldwide due to its complexity and difficulty in early-stage diagnosis and target therapy. Modern strategies of OVCA treatment involve debulking surgery combined with chemotherapy. Nonetheless, present treatment is far from satisfactory sometimes and therefore the demand for novel therapeutic measures needs to be settled. Pyroptosis is a notable form of programmed cell death characterized by influx of sodium with water, swelling of cells and finally osmotic lysis, which is distinctive from numerous classes of programmed cell death. So far, four major pathways underlying mechanisms of pyroptosis have been identified and pyroptosis is indicated to be connected with a variety of disorders including cancerous diseases. Interestingly enough, pyroptosis is in relation to ovarian cancer with regard to long non-coding RNAs and several regulatory molecules, as is shown by previously published reports. In this review, we summarized major pathways of pyroptosis and the current research foundations of pyroptosis and ovarian cancer, anticipating enriching the thoughts for the treatment of ovarian cancer. What’s more, some problems yet unsolved in this field were also raised to hopefully propose several potential threads of OVCA treatment and research directions in future.